Effect of L. casei CRL 431 and its cellular wall on the thymus at different ages in a mice model - Balcells, Maria Florencia (2018)
The thymus is a primary lymphoid organ, where ontogeny and maturation of T lymphocytes occurs, however, it begins to regress with time.Aim: to study the effect of L. casei 431 and/or its cell wall in the thymus at different ages.BALB/c mice were divided into groups according to age: 21, 28, 45, 90 and 180 days(d), which were subdivided according to the supplement they received from the first day: Normal control (NC) who received the conventional balanced diet and water ad libitum, Lactobacillus casei (Lc) that received the conventional balanced diet and suspension of L. casei 431. Mice were sacrificed at the corresponding age. Initial and final weight of the animal, weight of the thymus was taken. The samples were: large intestine for microbiota analysis, serum (S), small intestinal fluid (IF) for cytokine analysis by ELISA (IFNγ, IL-6, IL-10, IL-12 p70, TNFα, IL-3) we also determined cytokines in the in vitro culture supernatant of thymus(T) stimulated with the bacterium complete (B) or its cell wall (W). T population in thymus, mesenteric lymph nodes (MLN) was analyzed by flow cytometry. Results: oral supplementation increased body weight in all groups. Body weight / thymus ratio decreased at 28, 45 and 90d in Lc. Supplementation showed decreased population of enterobacteria and increased the population of lactobacilli. We did not observe significant differences between NC and LC in the total anaerobic population.Cytokines in cell culture supernatant showed a decrease in IFNγ and TNFα, increased values of IL-10, IL-12 and IL-3, and we observed tendency to normalize IL-6 values of TB in Lc. The immune cells in Lc group in Timo, at 45d showed decrease in CD4+ populations, and significantly increased at 90d respect to NC, while we observed in NC CD4+/CD8+ population a significant increase at 90d (p <0.05) respect to LC (90d CD4+/CD8+: NC = 80.72 ± 0.32, LC = 0.45 ± 0.06).Oral supplementation and in vitro stimulation with complete bacteria and/or its cell wall produced effects in the thymus at different periods of time in mice.